Effect of Early Marriage on Girl-Childâ€™s Further Education in Okpokwu Local Government Area, Nigeria: Implications for Counseling - Ugboha, Grace Onyowo; Namo, Ibuebue Sarah (NIU Journal of Humanities, 2019)
This study investigated the impact of early marriage on girl-childâ€™s further education in Okpokwu Local Lovernment Area, Nigeria. It employed a descriptive survey design. Two research questions were asked and two hypotheses were tested at 0.05 level of significance. The sample size of 300 females was employed using the specification of Research Advisor (2006). A self-developed instrument titled, â€œImpact of Early Marriage Scale (IRMGCFES)â€ was adopted for the study. The instrument was administered by the researcher by personal visit to the sampled schools. The data collected were analyzed using chi-square statistics tested at 0.05 level of significance. The results showed that early marriage has a significant impact on girl-childâ€™s further education in Okpokwu Local Government Area, Nigeria. The study recommended that awareness about the issue should be raised, and the government should make the laws concerning it stricter. Keywords : Early marriage, Girl-child, Further education, Okpokwu Local Government Area.